2014
DOI: 10.1021/jm4016894
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Preclinical Characterization of the Cyclopropylindolobenzazepine BMS-791325, A Potent Allosteric Inhibitor of the Hepatitis C Virus NS5B Polymerase

Abstract: Described herein are structure-activity relationship studies that resulted in the optimization of the activity of members of a class of cyclopropyl-fused indolobenzazepine HCV NS5B polymerase inhibitors. Subsequent iterations of analogue design and syntheses successfully addressed off-target activities, most notably human pregnane X receptor (hPXR) transactivation, and led to significant improvements in the physicochemical properties of lead compounds. Those analogues exhibiting improved solubility and membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 82 publications
1
67
0
Order By: Relevance
“…The activity assays show that the NS5B-inhibitor complex reaches equilibrium faster with L30S compared with WT but that the variant has no impact on inhibitor potency. X-ray co-crystals show that the same finger loop is displaced by the binding of BMS-791325 in the thumb pocket (10). The structural data combined with our inhibition data suggested that the finger loop "competes" with BMS-791325 for binding to the thumb pocket, and thus, the L30S variant was used to probe the impact of the finger-thumb interaction on BMS-791325 binding kinetics.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The activity assays show that the NS5B-inhibitor complex reaches equilibrium faster with L30S compared with WT but that the variant has no impact on inhibitor potency. X-ray co-crystals show that the same finger loop is displaced by the binding of BMS-791325 in the thumb pocket (10). The structural data combined with our inhibition data suggested that the finger loop "competes" with BMS-791325 for binding to the thumb pocket, and thus, the L30S variant was used to probe the impact of the finger-thumb interaction on BMS-791325 binding kinetics.…”
Section: Discussionmentioning
confidence: 68%
“…In a more recent Phase 2 study, 63 of 66 HCV-infected GT-1 patients treated for 12 or 24 weeks with a combination of BMS-791325 (75 or 150 mg twice daily), daclatasvir (60 mg once daily), and asunaprevir (200 mg twice daily) achieved sustained virologic response (9). The preclinical profile of BMS-791325, including potent activity in GT-1a and -1b enzyme and replicon assays (IC 50 and EC 50 values of 0.7-4 nM), selection of significant resistance at a single substitution site, and a robust pharmacokinetic profile in animal models, anticipated the strong antiviral effect observed in patients (10,11).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 94%
See 3 more Smart Citations